2009
DOI: 10.1089/hum.2008.137
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Relevant Effects of Convection-Enhanced Delivery of AAV2-GDNF on the Dopaminergic Nigrostriatal Pathway in Aged Rhesus Monkeys

Abstract: Growth factor therapy for Parkinson's disease offers the prospect of restoration of dopaminergic innervation and/or prevention of neurodegeneration. Safety and efficacy of an adeno-associated virus (AAV2) encoding human glial cell-derived neurotrophic factor (GDNF) was investigated in aged nonhuman primates. Positron emission tomography with 6-[18F]-fluoro-l-m-tyrosine (FMT-PET) in putamen was assessed 3 months before and after AAV2 infusion. In the right putamen, monkeys received either phosphate-buffered sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 60 publications
5
57
0
Order By: Relevance
“…However, a randomized, placebo-controlled trial that showed limited benefit did not achieve efficacy end-points (Lang et al, 2006) for reasons that may relate to adequate distribution of infused GDNF within the target putamen (Gimenez et al, 2011). In light of delivery-related problems, use of gene therapy for delivery of GDNF to the nigrostriatal system is now under consideration (Johnston et al, 2009;Kells et al, 2012). Another possible explanation for the variable results is inadequate GM1 in the affected neurons.…”
Section: Introductionmentioning
confidence: 99%
“…However, a randomized, placebo-controlled trial that showed limited benefit did not achieve efficacy end-points (Lang et al, 2006) for reasons that may relate to adequate distribution of infused GDNF within the target putamen (Gimenez et al, 2011). In light of delivery-related problems, use of gene therapy for delivery of GDNF to the nigrostriatal system is now under consideration (Johnston et al, 2009;Kells et al, 2012). Another possible explanation for the variable results is inadequate GM1 in the affected neurons.…”
Section: Introductionmentioning
confidence: 99%
“…30 Vectors derived from adeno-associated viruses (AAV) elicit little, if any, damage or inflammatory response after intracerebral injection, and may deliver long-term transgene expression to non-dividing cells in multiple tissues, including the brain in rodents and in monkeys. [31][32][33][34][35][36][37][38] However, the size of the transgene inserted must be smaller than 4 kb. AAV tropism and transduction efficiency can be modified by using different AAV serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The neuroprotective effects of GDNF were then further confirmed using an AAV2-GDNF viral vector in unilaterally 6OHDA-lesioned marmosets where the viral vector was delivered into the SN 4 weeks before lesioning (Eslamboli et al, 2003b;Eslamboli et al, 2005). More data was accumulated in healthy aged and unilaterally lesioned MPTP monkeys and results showed an improvement in clinical score and in [ 18 F]-FMT uptake in the injected putamen in PET scans Johnston et al, 2009;Kells et al, 2010). Although these results were robust and replicated in different laboratories, the predictive value of such an improvement is conditioned to the models used to tests it: intact aged monkeys or monkeys bearing unilateral lesions in order to use the contralateral hemisphere as an internal control are not representative of the clinical situation.…”
Section: Gene Therapymentioning
confidence: 91%